the The instructor and project training at SENA - Zapata, Liliam
As a methodological strategy in SENA, training by projects has been worked on since the 1990s and, although it has been recognized in the framework of training by labor competencies, it is necessary to retake its foundations and the way in which it is day-to-day it is constituted and rebuilt as part of the pedagogy strategy assumed by SENA from the guidelines of UNESCO and its four pillars: learning to know, learning to do, learning to live together, learning to be (Delors, nd). Without attempting to make this article a pedagogical dissertation on the project method, it contains the essential elements that reaffirm the work of the SENA instructor in the daily routine and enrich and strengthen the strategy within the framework of its mission: "Training for productive work ”, Analyzing, at least from experience, the challenges that the project method represents for the entity and the instructors.